American Society for Enhanced Recovery and Perioperative Quality Initiative Joint Consensus Statement on the Role of Neuromonitoring in Perioperative Outcomes: Electroencephalography. (May 2020) - Chan, Matthew T. V.; Hedrick, Traci L.; Egan, Talmage D.; García, Paul S.; Koch, Susanne; Purdon, Patrick L.; Ramsay, Michael A.; Miller, Timothy E.; McEvoy, Matthew D.; Gan, Tong J.
Abstract : Electroencephalographic (EEG) monitoring to indicate brain state during anesthesia has become widely available. It remains unclear whether EEG-guided anesthesia influences perioperative outcomes. The sixth Perioperative Quality Initiative (POQI-6) brought together an international team of multidisciplinary experts from anesthesiology, biomedical engineering, neurology, and surgery to review the current literature and to develop consensus recommendations on the utility of EEG monitoring during anesthesia. We retrieved a total of 1023 articles addressing the use of EEG monitoring during anesthesia and conducted meta-analyses from 15 trials to determine the effect of EEG-guided anesthesia on the rate of unintentional awareness, postoperative delirium, neurocognitive disorder, and long-term mortality after surgery. After considering current evidence, the working group recommends that EEG monitoring should be considered as part of the vital organ monitors to guide anesthetic management. In addition, we encourage anesthesiologists to be knowledgeable in basic EEG interpretation, such as raw waveform, spectrogram, and processed indices, when using these devices. Current evidence suggests that EEG-guided anesthesia reduces the rate of awareness during total intravenous anesthesia and has similar efficacy in preventing awareness as compared with end-tidal anesthetic gas monitoring. There is, however, insufficient evidence to recommend the use of EEG monitoring for preventing postoperative delirium, neurocognitive disorder, or postoperative mortality.